Illiteracy a Social Issue: And it’s Remedial Measures: Exploring the Link between Illiteracy and Poverty: Strategies for Improvement (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Illiteracy is one of the major problems that are faced by the every corner of the world. Many developing countries like India are adversely affected by the basic social problems – poverty, illiteracy and unemployment. These problems are the greatest challenges in the path of the development. As the problem of illiteracy in India is concerned, it is an established fact that India is one of the least literate countries of the world. There are a number of individuals, communities and social groups who are not able to acquire minimum standard level of education. The major effect of illiteracy in India is poverty. Poverty is a problem for both the developing and the developed countries. It can be understood from three perceptions these are basic needs, income and capability. An individual is avowed to be under poverty when his income is below a certain point. When an individual is not able to meet these requirements such as adequate nutrition, shelter, clothing, healthcare, education, and then he is stated to be residing within the conditions of poverty. In this paper researcher highlight the firm relationship between illiteracy and poverty and also discuss about the measures in the problem of illiteracy.